Perancangan Sistem Value Chain terhadap Prospek Pengumpulan E-Waste di Bank Sampah - Stephanus Kelvin; Helena J. Kristina; Eric Jobiliong (Universitas Katolik Parahyangan, 2016)
Electronic waste (e-waste) has become environmental issue in Indonesia. Several tons of e-waste was generated each year. Available landfills will not be sufficient to accommodate e-waste that people produce. Waste bank become one of many solutions to overcome this problem. Implementation of pilot project in waste bank is needed to see the prospects of e-waste collection in waste bank. Thus, the goal of this research is to design a value chain system for e-waste collection prospect in waste bank and system simulation as the foundation for implementing a pilot project. Simulations on 2 scenarios had been done to determine profitability of e-waste collection’s pilot project in waste bank. Based on simulation, it is known that there is profit generated from e-waste recycling process for 2 scenarios. Ranges of profit for 2 months are Rp. 7.963.879 - Rp. 40.447.047 for scenario 1 and Rp. 7.952.394 – 40.435.561 for scenario 2. If only PCB component that could be recycled, profit for 2 months still can be generated in the range Rp. 689.964 – Rp. 6.398.486 for scenario 1 and Rp. 678.478 – Rp. 6.387.000 for scenario 2. Thus, implementation of e-waste collection’s pilot project in waste bank is profitable.